Poly-P-forming characteristics found in poly-P-accumulating microorganisms (phosphate-accumulating organisms [PAOs]) isolated from shrimp ponds in Vietnam - Tran Thi Huyen; Ha Phuong Trang; Pham Thi Kim Phan; Trinh Ngoc Nam (Fisheries and Aquatic Sciences)
Significant amounts of phosphate (PO43–) in extensive shrimp ponds make an ideal survey for studying the PO43–-accumulating properties of phosphate-accumulating organisms (PAOs) and harvesting polyphosphate (poly-P). In this study, we evaluated the PO43–-accumulating capacities of four PAOs (A1, A2, A3, and A5) from those ponds by determining the residual PO43–-content in acetate mineral mediums (AMM) with/without NaCl at different inoculated periods. Strain A2 was identified as a Rhodotorula sp., whereas strain A1 was Acinetobacter guillouiae, A3 was Acinetobacter lwoffii, and A5 was Lactococcus raffinolactic. Among four PAOs, strains A1 and A5 showed the highest PO43–-accumulating capacities of 338.44 and 333.63 μg in 100 mL of AMM, respectively, after 72 hours under cultural AMM without adding NaCl. All PAOs might extend the inoculation periods to 120 hours for mostly PO43–-accumulations in the AMM with NaCl contents (5%–30‰) (p < 0.05). The PO43–-accumulation levels from 338.40 to 285.55 μg of Acinetobacter guillotine demonstrated significantly higher capacities than the remaining PAOs (p < 0.05), whereas the maximum PO43–-collections of L. raffinolactic with 281.65 μg/100 mL recognized at single condition of NaCl content of 20‰, followed with 279.70 μg/100 mL by A. lwoffii at a NaCl content of 10‰. Upon the rate of PO43–-accumulation correlated with growths in the LB medium with different salinities combined, the activities of the four PAOs did not alter the pH of the AMM, around 6.5 to 7.0, providing evidence for the impressing PO43–-accumulating capacities of four PAO strains on different survival media conditions. This study is the first report on the accumulation of PO43– to forming polyphosphate (poly-P) chains in L. raffinolactic cells; the other strains poly-P granules generated inside cells. Remarkably, our findings comprehensively discovered the forming process of poly-P in A. guillotine cells through image analysis at three inoculation times (0, 24, and 72 hours). These PAOs are viable probiotics that bring advantages in lowering abundant PO43–-compounds in aquaculture wastewater and treating different PO43–-polluted water resources. The poly-P in PAO cells promises valuable sources for harvesting poly-P applied in the fertilizer industry or biominerals.